Faktor Penghambat Pelayanan Kesehatan Rutin di Rumah Sakit saat Pandemi COVID-19 - Intan Resvilani; Inge Dhamanti (STIKes Hang Tuah Pekanbaru, 2021)
The COVID-19 pandemic has caused some disruptions on regular health services at hospitals. This study identified barrier in regular health services in hospitals. This study was used scoping review method. The search for articles was carried out through the Science Direct, PubMed, and Google Scholar database. Â The keywords were â€œregular health servicesâ€ AND â€œhospitalsâ€ AND â€œbarriersâ€ AND â€œCOVID-19â€and obtained a total of 66. Total of 4 articles that met the inclusion criteria were analyzed. The studies included were originated from several hospitals in four countries which showed inhibiting factors that affect regular health services. The most common factors found were related to organizations such as a lack of health human resources, lack of adaptation to the latest technology, lack of adaptation to hospital policies, and limited hospital facilities, infrastructure, and facilities. Hospitals need to maintain the sustainability of regular health services by evaluating service priorities, meeting the needs of health workers, facilities, and infrastructure.